Emergency Department Evaluation of Traumatic Brain Injury in the United States, 2009–2010. Issue 6 (November 2016) - Korley, Frederick K.; Kelen, Gabor D.; Jones, Courtney M.; Diaz-Arrastia, Ramon
Abstract : Objective: To determine the dimensions of traumatic brain injury (TBI) evaluation in US emergency department (EDs) to inform potential application of novel diagnostic tests. Setting: US EDs. Participants: National Hospital Ambulatory Medical Care Survey of ED visits in 2009 and 2010 where TBI was evaluated (1) and diagnosed either clinically or (2) with head computed tomographic (CT) scans. Design: Retrospective cross-sectional. Results: TBI was evaluated during 4.8 (95% confidence interval [CI], 4.2-5.4) million visits per year; and head CT scan was performed in 82% of TBI evaluations (3.9 [95% CI, 3.4-4.4] million visits per year). TBI was diagnosed in 52% of evaluations (2.5 [95% CI, 2.1-2.8] million visits per year). Among those who received head CT scans, 9% had CT evidence of traumatic abnormalities. Among patients evaluated for TBI who had a Glasgow Coma Scale score recorded, 94.5% were classified as having mild TBI, 2.1% as moderate TBI, and 3.5% as severe TBI. Among patients with International Classification of Diseases, Ninth Revision, Clinical Modification, codes permitting the calculation of head Abbreviated Injury Scale scores 9.0%, 85.0%, 2.5%, 3.2%, 0.3%, and 0% had head Abbreviated Injury Scale scores of 1, 2, 3, 4, 5, and 6, respectively. Of patients evaluated for TBI, 31% had other head/face/neck injuries, 10% had spine and back injuries, 7% had torso injuries, and 14% had extremity injuries. Conclusion: The ED is the main gateway to medical care for millions of patients evaluated for TBI each year. Novel diagnostic tests are needed to improve ED diagnosis and management of TBI.